Associations Between Psychological Profiles and Performance Success Among Professional Taekwondo Athletes in China: A Multidimensional Scaling Profile Analysis - Li, Bing; Ding, Cody; Fan, Fenghui; Shi, Huiying; Guo, Liya; Yang, Feng (Frontiers in Psychology, 2020)
What leads to an optimal psychological state for peak performance has been a topic of research in sport psychology for a long time. A persistent question has been whether there is a group of ideal mindsets or factors that are required to achieve optimal performance, and if there are, what are they and how are they related to the latter. To answer these questions, the current study aimed to identify potential profiles of personality and emotional traits based on a sample of professional Taekwondo athletes from China. It also aimed to examine the utility of the profiles in predicting athlete performance success. Using the multidimensional scaling (MDS) profile analysis, two latent profiles of personality and emotional traits were identified, which indicate four subtypes of athletes. Regression analyses were conducted to examine how the identified profiles were associated with performance success. The results seemed to suggest that Taekwondo athletes with more performance success were more likely to have a profile of positive personality and emotional traits, while athletes with less performance success were likely to have somewhat elevated levels of self-control, extraversion, and aggression. Knowledge of athletes’ personality profiles will help sport psychologists develop suitable interventions to enhance athletes’ performance success. These results were discussed in the context of athlete psychosocial development.